THE INFLUENCE OF BRAND AMBASSADOR AND BRAND IMAGE ON PRODUCT PURCHASE DECISIONS - Dede Suleman; Fahira Adya Prasetyo (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the effect of brand ambassadors and brand image on purchasing decisions for Nature Republic products at Kpopers in the Cheries Group Chat. The method used in this research is quantitative research with associative method with a total sample of 145 respondents. The analytical technique used to process SPSS 25 software. The results of this study indicate that the brand ambassador has a positive and significant effect on purchasing decisions with the acquisition of a statistical t table of 2.398 > 1.97635 and 0.018 < 0.05. Then, brand image has a positive and significant effect on purchasing decisions with the acquisition of a statistical t table of 7.999 > 1.97635 and a significant value of 0.000 < 0.05.